If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11w + -8 = 3 Reorder the terms: -8 + 11w = 3 Solving -8 + 11w = 3 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 11w = 3 + 8 Combine like terms: -8 + 8 = 0 0 + 11w = 3 + 8 11w = 3 + 8 Combine like terms: 3 + 8 = 11 11w = 11 Divide each side by '11'. w = 1 Simplifying w = 1
| 4/6c=7 | | 2(28)+6=0 | | -10-4w+2w-4-5+10w= | | ab-cb=h | | 6-8=2+9-1 | | x+26=18 | | -9+8x=33+5x | | ((c^2d^(-1/2)/c^-1d^(2/3))^(-2/5) | | (2*7)4+8-7= | | 6N-1+5N=3N+15 | | -6-5v-9x-6x+2v= | | -10y-7=-1 | | 10x+28=3x | | 6-6=(1/3)(3-3) | | 7y+3=2y+23 | | -10b+6-5b= | | 6-6=1/3(3-3) | | n^2+12n=-35 | | F(x)=0.75x+80 | | -3y+8=2 | | -3x-y= | | 2d-3=51 | | 1/2x=4=3/4(2x-8) | | 10(2y+2)y=2(8y-8) | | b^2+12=7b | | 3(1+2x)+5=13+5x | | 204(x+2x)+75=795 | | p^2-32=-4p | | 2(1)=2(1)-12 | | C+1523=2766 | | 3(x-7)=-6(x+8) | | 3x+5=2(2x-1)*(x-3) |